The Shrinking Space of Civil Society: a Report on Trends, Responses, and the Role of Donors - Ayvazyan, Karen (2019)
Abstract: Civil society is one of the main arenas of the democratization. However, in recent years the political space of civil society has become narrower and does not contribute to effective operation of civil society organisations (CSOs). Due to repression by governments, civil society organisations are encountering a series of challenges, which may extend to closing down the organisations. Civil society activists are being violently attacked, imprisoned and/or forced to emigrate. The mutual mistrust and the lack of dialogue between CSOs and government is increasing, not only in authoritarian, but also in some democratic states across the world. This study aims to promote the importance of dialogue between civil society and governments in preventing the repression of civil society. Moreover, it will investigate the nature and causes of repression of civil society, to identify trends of shrinking the space as applied by states, to explore the responses and impact of shrinking space on civi